Capturing the complexity of conflict. Dealing with violent ethic conflicts of the post-cold war era - SANDOLE, Dennis J D (Pinter Publishers, 1999)
Capturing the complexity of comflict. Dealing with violent ethnic conflicts of the post-cold.